Non-Coding RNA and Frizzled Receptors in Cancer - Smith, Alex J.; Sompel, Kayla M.; Elango, Alamelu; Tennis, Meredith A. (Frontiers in Molecular Biosciences, 2021)
Frizzled receptors have been long recognized for their role in Wnt/-catenin signaling, a pathway known for its tumorigenic effects. More recent studies of frizzled receptors include efforts to understand non-coding RNAs (ncRNA) regulation of these receptors in cancer. It has become increasingly clear that ncRNA molecules are important for regulating the expression of both oncogenic and tumor suppressive proteins. The three most commonly described ncRNA molecules are microRNAs (miRNA), long non-coding RNAs (lncRNA), and circular RNAs (circRNA). Here we review frizzled proteins and ncRNA molecules that directly or indirectly affect frizzled protein expression and downstream signaling. Exploring these interactions highlights the potential of incorporating ncRNA molecules into cancer prevention and therapy strategies that target frizzled receptors. Previous investigations of frizzled receptors and ncRNA have established strong promise for a role in cancer progression, but additional studies are needed to provide the substantial pre-clinical evidence required to translate findings to clinical applications.